P1858PSYCOEDUCATIONAL TEAM IN PRE- HEMODIALYSIS FOR PATIENTS AND CAREGIVERS. (6th June 2020) - Mulè, Marica; Gaggia, Paola; Movilli, Ezio; Manenti, Chiara; Appiani, Miriam; Zani, Orietta; Bertoni, Anna; Scolari, Francesco
Abstract: Background and Aims: The aim of this work is to explain the training to create a multidisciplinary team that in the future will activate the psychoeducational groups in nephrology. These groups will be support to patients and caregivers already in the waiting period from the intervention of the fistula at the beginning hemodialysis. Method: The training of five meetings was realized from March 2019 to May 2019. The training for a team composed by 3 nephrologist, 4 nurses, 1 dietician, 1 nursing coordinator was conducted of a psychologist to established modalities and aims of a psychoeducational pathway for patients that will begin hemodialysis and their caregivers. In the first meeting, through a focus group, the participants discussed the word "to cure". In the second meeting participants defined patient and caregiver's needs after the diagnosis of Chronic Kidney Disease. In the third meeting the team work defined the objectives and methods of conducting future groups psychoeducational. In the fourth meeting participants decided the duration and modalities of the psychoeducational pathway for patient and caregiver. Finally, in the fifth meeting, the team reviewed the objectives, recipients and thematic areas of the meetings for patients and caregivers. In addition, an evaluation questionnaire was administered to verify the benefit and satisfaction of the training. All the contents of the training were transcribed in a diary and analyzed with a pencil and paper mode. Results: In the first meeting the team discussed the need to accompany and educate patients even before the onset of haemodialysis. In the second meeting team decided that the therapeutic education is not only for patients waiting to start haemodialysis but also on their caregivers often uninformed and not involved by doctors and nurses. In this focus the caregiver appears an important figure that support the patient at home and if not properly informed it can become an obstacle in patient care. In the fourth and fifth meetings have been defined a possible psychoeducational training in three total meetings so named: Knowing each other differently: to get to know both the patient and the caregiver in an active listening setting. Knowing dialysis concretely : to know better the treatment and pay attention to the care of your psychological well-being too. Knowing the diet actively: to inform and support the patient and caregiver of future and current changes in eating habits. The participants in the satisfaction questionnaire to the question "how much did this training respond to the needs of your job?" on nine answers collected, the outcome it was M = 4.7 on Likert scale 1(few)-5 (much). Conclusion: The training has managed to build a multidisciplinary team ready to care patients and caregivers that will begin haemodialysis in a more informed and aware way. Currently, two psychoeducational groups have been created for patient and caregiver. As shared in the multidisciplinary team's training these psychoeducational groups are activated to help the patient to accept dialysis at the same time help the family member to take on the role of caregiver. This project has made it possible to improve not only teamwork but overall patient and caregiver care.